(untitled) - Kottler, Jeffrey A. (San Francisco, CA, 2006)
It is an excellent book that highlights the suffering and pain that coexist in parallel with extraordinary creativity
Keywords: Mental illness,Mental illness,Genius and mental illness,Art and mental illness,Bệnh tâm thần